Upaya Mengembangkan Pengendalian Emosi melalui Metode Bercerita pada PAUD Duyun Desa Bungabali Kec. Pantar Timur - Imanuel Puling (Inovasi Pendidikan dan Anak Usia Dini, 2026)
This study, entitled "Developing Emotional Control Skills in Early Childhood Education (PAUD) Duyun in Bungabali Village, Pantar Timur District," found that children still struggle to manage their emotions, such as irritability, excessive crying, and difficulty interacting positively with peers. Therefore, effective and enjoyable efforts are needed to help children control their emotions, one of which is through storytelling. This study aims to develop children's emotional control through the application of storytelling to early childhood education at PAUD Duyun. The research method used is a descriptive (exploratory) approach, based on objective observation of a social phenomenon. In this case, the research compiles or creates a clearer picture while data is collected and parts are tested. The results are expected to demonstrate that the application of storytelling can improve children's ability to recognize, express, and control emotions more positively. Furthermore, storytelling activities can also create a fun and interactive learning environment, making it easier for children to understand the emotional values ​​conveyed.